Adoption and correlates of Western concepts of high performance work system in the IT industry in India. Issue 4 (5th September 2016) - Singh, Ajay; Singh, Gangaram; Beatty, James R.
Abstract : Purpose: An interesting conundrum exists in India with its rise as an economic powerhouse. On one front, there is tremendous pride in asserting its Indian identity. On another front, it seeks to embrace Western practices to announce its entry into the world economy. This paper aims to examine the extent to which Indian information technology (IT) firms adopt Western concepts of a high performance work system (HPWS) and the correlates of such a system (pro-social organizational behavior and employee attitude). Data from 211 IT employees in India show widespread adoption of a HPWS, and more importantly several approaches to assessment indicate that a HPWS positively correlates to pro-social organizational behavior and employee attitude. Design/methodology/approach: The sample consisted of IT professionals in India having a minimum of three years of work experience. The study has used a snowball strategy to generate the sample. Eight HPWS practices were included in the survey questionnaire to assess three dimensions of HPWS. Analysis was conducted to examine differences between the highest (i.e. top 10 per cent) and the lowest (i.e. bottom 10 per cent) and bivariate correlations of the surveyed employees regarding pro-social organizational behaviors related to altruism, job involvement and work involvement, and regarding employees attitudes related to job satisfaction, intention to stay in organization, level of morale and optimism. Findings: HPWS is positively associated with employee attitudes and pro-social organizational behavior. It reflects the reality that HPWSs, at least as conceived by researchers from the West, have penetrated organizations in India. Moreover, they seem to complement each other and together they seem to have a positive association with employee attitudes and pro-social organizational behavior. As organizations in India continue with the march toward servicing the world in the IT sector, the present study suggests that they have a potent tool in a HPWS to keep employee attitudes and pro-social organizational behaviors high. Research limitations/implications: The criticism of survey methodology approach adopted in the present study is that it has common method bias. That is, in the survey, respondents tend to score along a path with a common response. As a validation, the study has performed a treatment-by-subjects analysis of variance with matched participant scores on the three pro-social behaviors to determine whether the means of altruism, job involvement and work involvement were significantly different. As to convergence, much more causal data would be needed to make a definitive conclusion on the findings of the present study. Originality/value: This is the first study of its kind to examine the adoption of Western concepts of a HPWS in Indian IT Industry.